A force measuring device developmentfor testing auto-coupling devices of the SA-3 type - Shalupina P.I (Научно-технический вестник Брянского государственного университета)
The article presents the results of the development of a force-measuring device for testing auto-coupling devices and absorbing devices of railway vehicles. The technical idea of the device is to physically measure the stresses acting in the characteristic cross sections of the tail of an auto-coupling device, followed by determining the actual force using the developed mathematical model. A calibration schedule of the force measuring device was constructed. The influence of additional bending moments on the measurement accuracy is estimated.